1988
DOI: 10.1093/ajcn/47.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starch structure on glucose and insulin responses in adults

Abstract: Twelve women and 13 men were given meals containing cornstarch with 70% of the starch in the form of amylopectin or amylose to determine if differences in glycemic response result from different chemical structure. Blood was drawn before and 30, 60, 120, and 180 min after each meal. The meals consisted of starch crackers fed at the rate of 1 g carbohydrate from starch per kilogram body weight. The amylose meal resulted in a significantly lower glucose peak at 30 min than did the amylopectin meal. Plasma insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(110 citation statements)
references
References 27 publications
6
99
1
2
Order By: Relevance
“…Factors affecting the rate of glucose absorption from starchy food and therefore the GI value include (1) the nature of the food and (2) the type and extent of food processing (Table 5). The former includes the ratio of amylose to amylopectin present in the raw food (Behall et al, 1988) and the type of monosaccharide components, the amount and type of dietary fiber (Jenkins et al, 1978), the presence of large amounts of fat or protein (Nuttall et al, 1984;Wolever et al, 1985;Collier et al, 1986;Bornet et al, 1987), antinutrients such as phytic acid, lectins and tannins (Yoon et al, 1983;Thompson et al, 1984;Rea et al, 1985) and nutrient -starch interactions in carbohydrate-containing foods, such as in wheat products (Jenkins et al, 1987a). Extrusion, flaking, grinding, canning, storing and cooking of the carbohydrate-containing foods can affect the particle size and the integrity of the starch granules (Jenkins et al, 1988a) and plant cell walls (Ellis et al, 1991), making the carbohydrate portion more accessible to digestive enzymes (Wolever, 1990;Collins et al, 1981).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Factors affecting the rate of glucose absorption from starchy food and therefore the GI value include (1) the nature of the food and (2) the type and extent of food processing (Table 5). The former includes the ratio of amylose to amylopectin present in the raw food (Behall et al, 1988) and the type of monosaccharide components, the amount and type of dietary fiber (Jenkins et al, 1978), the presence of large amounts of fat or protein (Nuttall et al, 1984;Wolever et al, 1985;Collier et al, 1986;Bornet et al, 1987), antinutrients such as phytic acid, lectins and tannins (Yoon et al, 1983;Thompson et al, 1984;Rea et al, 1985) and nutrient -starch interactions in carbohydrate-containing foods, such as in wheat products (Jenkins et al, 1987a). Extrusion, flaking, grinding, canning, storing and cooking of the carbohydrate-containing foods can affect the particle size and the integrity of the starch granules (Jenkins et al, 1988a) and plant cell walls (Ellis et al, 1991), making the carbohydrate portion more accessible to digestive enzymes (Wolever, 1990;Collins et al, 1981).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Another hypothesis to explain the effects of this starch on plasma lipids concerns its effect on insulin and glucagon levels, since the intestinal hydrolysis of amylose-rich starch and therefore the glucose release are slow. Indeed, glucose and insulin responses were decreased when the amylose content of rice starch [22] and cornstarch [23,24] was increased. Moreover O'Dea et al showed that the insulin response after a meal was closely related to the starch digestibility tested in vitro [25].…”
Section: Discussionmentioning
confidence: 99%
“…process [46], of which the main factor affecting starch digestibility is attributed to the ratio of amylose: amylopectin [2]. The ratio of amylase : amylopectin in the A-type starch granules is higher than that in the B-type starch granules, approximately 30%…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is the main source of energy for human consumption which represents up to 80% of daily caloric intake. Starch variation also has a wide range of impacts on human health [1][2][3]. World annual starch production from cereals is approximately 2,050 million tonnes [4], which are widely used in fields such as plastic, pharmacy, building, and textile [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%